Lack of Prenylated Proteins, Autophagy Impairment and Apoptosis in SH-SY5Y Neuronal Cell Model of Mevalonate Kinase Deficiency. - Tricarico, Paola Maura; Romeo, Alessandra; Gratton, Rossella; Crovella, Sergio; Celsi, Fulvio (Cell Physiol Biochem, 2017)
BACKGROUND/AIMS: Mevalonate Kinase Deficiency (MKD), is a hereditary disease due to mutations in mevalonate kinase gene (MVK). MKD has heterogeneous clinical phenotypes: the correlation between MVK mutations and MKD clinical phenotype is still to be fully elucidated. Deficiency of prenylated proteins has been hypothesized as possible MKD pathogenic mechanism. Based on this hypothesis and considering that neurologic impairment characterizes Mevalonic Aciduria (MA), the most severe form of MKD, we studied the effects of I268T and N301T MVK mutations on protein prenylation, autophagy and programmed cell death in SH-SY5Y neuroblastoma cell lines. METHODS: SH-SY5Y cells were transiently transfected, with the pCMV-6 plasmid containing MVK wild type and the two mutated sequences. Protein prenylation levels were evaluated using GFP-RhoA-F to assess farnesylation, and GFP-RhoA to evaluate geranylgeranylation; autophagy was measured by evaluating LC3 and p62 protein levels, while Annexin V-FITC and Propidium Iodide staining allowed apoptosis detection. RESULTS: MVK mutants' over-expression causes decreased levels of farnesylation and geranylgeranylation, and also increased LC3 lipidation in SH-SY5Y, with concomitant p62 accumulation. Treatment with bafilomycin A1 (an inhibitor of vacuolar H+-ATPase, a late autophagy inhibitor) further increase LC3-II and p62 levels, suggesting that degradation of autophagolysosome could be impaired. SH-SY5Y, with both MVK mutants, showed apoptosis increase; the presence of N301T associated with augmented cell death. CONCLUSIONS: We hypothesize that mevalonate pathway impairment causes alteration of farnesylation and geranylgeranylation proteins and alteration of the autophagic flux; these changes can induce apoptosis, possibly more relevant in the presence of N301T mutation.
Keywords: Animals; Apoptosis; Autophagy; Cell Line, Tumor; Macrolides; Mevalonate Kinase Deficiency; Microtubule-Associated Proteins; Models, Biological; Mutation; Phosphotransferases (Alcohol Group Acceptor); Protein Prenylation; Rats